Composite ceramic material with shell-like structure and prefabricated compressive stress and preparation method thereof
Through layer-by-layer freezing method and hot press sintering process, combined with the phase change toughening mechanism of nanozirconia particles, a composite ceramic material with prefabricated compressive stress was designed, which solved the brittleness problem of ceramic materials and significantly improved its strength and toughness.
Patent Information
- Application Number
- CN202311283236.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-09-28
AI Technical Summary
The inherent brittleness of ceramic materials leads to insufficient strength and damage tolerance, and the prior art is difficult to effectively improve the toughness and strength of ceramic materials at the structural level.
Through layer-by-layer freezing method and hot press sintering process, a composite ceramic material imitating shell structure with prefabricated compressive stress was designed, and a multi-layered "brick mud" structure was constructed with the phase change toughening mechanism of nanozirconia particles.
The mechanical properties of ceramic materials are significantly improved, including strength and fracture toughness, so that they can withstand higher tensile stresses and achieve better comprehensive mechanical properties.
Smart Images

Figure CN117263661B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite structure ceramic materials, and in particular relates to a shell-like structure composite ceramic material with prefabricated compressive stress and a preparation method thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Ceramic materials are widely used in various fields due to their high strength, high hardness, high wear resistance, high corrosion resistance, high insulation, high temperature stability, etc. In structural engineering, ceramic materials are often used to manufacture high-temperature parts, wear-resistant parts, ceramic cutting tools, etc. In the field of electronics, ceramic materials are widely used in electronic components, capacitors, piezoelectric devices, etc. In addition, ceramic materials also play an important role in medical, energy, environmental protection and other fields. However, due to the intrinsic brittleness of ceramic materials, their safety is greatly reduced. Therefore, researchers have been committed to developing new ceramic materials, improving preparation processes and processing technologies to improve the toughness, strength and machinability of ceramic materials.
[0004] In order to overcome the existing problems, scientists and engineers have been committed to developing various methods to increase the toughness of ceramic materials. These include particle toughening, fiber toughening, whisker toughening, phase transformation toughening, interface controlled toughening, grain size control, and residual compressive stress toughening. Among them, prestressed ceramics are a material with special mechanical properties. The method of introducing residual compressive stress in the surface layer to improve the strength and damage tolerance of brittle ceramics is more attractive due to its significant strengthening effect and convenience. For ceramic materials, their tensile strength is significantly lower than their compressive strength. Most failures originate from surface defects. If compressive stress is introduced in the surface layer, the crack initiation and propagation caused by these defects will be inhibited. In previous studies, prestressing has been widely used to improve the strength of concrete and tempered glass, but related research in ceramic materials has not been carried out in depth. The fracture of ceramics is mainly caused by crack propagation in the surface layer. Therefore, the key to improving the strength and damage tolerance of ceramics is to increase the resistance to surface crack propagation. By designing the material so that the surface material has a low thermal expansion coefficient and the matrix material has a high expansion coefficient, compressive stress is generated in the surface layer of the sample after the sintering process. The generated compressive stress hinders the crack propagation and can resist higher tensile stress, thereby improving the strength and damage tolerance of the ceramic.
[0005] In addition to pre-fabricating compressive stress into the material, improving the comprehensive mechanical properties of the material through structural design of ceramic materials is also an effective means. Molluscs in nature, such as abalone, use their shells to resist the invasion of natural enemies and protect their soft tissues. The nacre in the shell can resist external impact and can withstand large inelastic deformation. Studies have found that the nacre is composed of 95vol% aragonite (CaCO3) and 5vol% organic materials (proteins and polysaccharides). Compared with its component calcium carbonate single-phase material, the fracture toughness is three to nine times higher. The reason is nothing more than the special microstructure of the shell nacre. The shell nacre is a "brick and mud" structure stacked by aragonite flakes and organic matter, similar to a city wall. Although the organic matrix in the nacre is only 5wt%, it plays an important role in the spatial and chemical control of crystal nucleation and growth, microstructure and toughness enhancement. The nacre of shells has been studied for decades due to its excellent mechanical properties, self-assembly ability and complex hierarchical structure, which spans from nanometers to millimeters. To this end, scientists hope to replicate this material with a special "brick and mud" structure, retaining the toughening mechanism at multiple scales, thereby improving the fracture toughness of the material.
[0006] The inventors found that in the prior art, more research tends to focus on how to replicate the structure of the shell nacre more perfectly, or to improve material performance by replacing material components, such as metals, polymer materials or inorganic reinforcements. Such methods are relatively limited and cannot further improve material performance at the structural level, and ignore the research methods of enhancing pure inorganic phase ceramic composite materials through multiple means. Summary of the invention
[0007] In order to solve the deficiencies of the prior art, the purpose of the present invention is to provide a composite ceramic material with a shell-like structure having prefabricated compressive stress and a preparation method thereof. The present invention makes it possible to combine the prefabricated stress of the material with the imitation shell nacre structure through the layer-by-layer freezing method, and constructs a composite ceramic material with a shell-like structure having a prefabricated compressive stress design by layered regulation of the material components and layer-by-layer freezing. The present invention applies these two types of strengthening and toughening methods to the material at the same time, so that the composite material has both better strength and toughness.
[0008] In order to achieve the above object, the present invention is implemented through the following technical solutions:
[0009] In a first aspect, the present invention provides a method for preparing a shell-like structure composite ceramic material with prefabricated compressive stress, comprising the following steps:
[0010] S1, adding nano-particle aluminum oxide, nano-particle zirconium oxide, sodium dodecyl sulfate, and polyvinyl pyrrolidone into deionized water, ball milling for the first time, then adding flaky aluminum oxide for the second ball milling, and after ball milling, dropping isooctyl alcohol to obtain a matrix layer slurry;
[0011] S2, adding nano-particle aluminum oxide, nano-particle zirconium oxide, sodium dodecyl sulfate, and polyvinyl pyrrolidone into deionized water, ball milling for the first time, then adding flaky aluminum oxide for the second ball milling, and after ball milling, dropping isooctyl alcohol into the mixture to obtain a surface layer slurry;
[0012] S3, pouring the surface layer slurry, the base layer slurry, and the surface layer slurry into the mold in sequence and freezing them, pouring and freezing the next time after each freezing, and freeze-drying the green body obtained by three freezing steps to obtain a green body;
[0013] S4, subjecting the green body to heat treatment to remove binder, and then subjecting it to hot pressing and sintering, to obtain the shell-like structure composite ceramic material with prefabricated compressive stress.
[0014] In the second aspect, the present invention provides a shell-like structure composite ceramic material with prefabricated compressive stress obtained by the preparation method as described in the first aspect, wherein the shell-like structure composite ceramic material with prefabricated compressive stress is composed of flaky alumina, nano alumina particles and nano zirconium oxide particles, the flaky alumina particle size is 5-11 μm, the nano alumina particle size is 60-90 nm, and the nano zirconium oxide particle size is 30-500 nm.
[0015] The beneficial effects achieved by one or more technical solutions of the present invention are as follows:
[0016] (1) The present invention obtains a prefabricated compressive stress design and a shell-like structure design by combining a layer-by-layer freezing and hot pressing sintering process. In addition, the introduced nano-zirconia particles provide a means of phase change toughening of the material and are filled between the alumina "bricks" as a toughening phase. The present invention obtains a shell-like structure composite ceramic material with prefabricated compressive stress through the gradient design of the material, and also has the phase change toughening provided by zirconium oxide, so that the mechanical properties of the material are significantly improved.
[0017] (2) The present invention combines a variety of strengthening and toughening methods to strengthen and toughen the material from the root from the perspective of structure and stress. The method is simple, the raw materials are cheap, and the whole process is environmentally friendly and pollution-free. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0019] Figure 1This is a design drawing of the shell-like structure composite ceramic material with prefabricated compressive stress in Example 1 of the present invention;
[0020] Figure 2 This is a SEM image of the surface layer of the shell-like structure composite ceramic material with prefabricated compressive stress in Example 1 of the present invention;
[0021] Figure 3 This is a SEM image of the matrix layer of the shell-like structure composite ceramic material with prefabricated compressive stress in Example 1 of the present invention;
[0022] Figure 4 The mechanical properties of the shell-like structure composite ceramic material with prefabricated compressive stress in Example 1 of the present invention;
[0023] Figure 5 This is a comparison chart of the mechanical properties of the prefabricated compressive stress shell-like structure composite ceramic materials of Examples 1 and 2 of the present invention and Comparative Examples 1-3. DETAILED DESCRIPTION
[0024] As introduced in the background technology, existing research tends to focus on how to replicate the structure of the shell nacre more perfectly, or to improve material performance by replacing material components, such as metals, polymer materials or inorganic reinforcements. Such methods are relatively limited and cannot further improve material performance at the structural level, ignoring the research methods of enhancing pure inorganic phase ceramic composite materials through multiple means.
[0025] A first typical embodiment of the present invention is a method for preparing a shell-like structure composite ceramic material with prefabricated compressive stress, comprising the following steps:
[0026] S1, adding nano-particle aluminum oxide, nano-particle zirconium oxide, sodium dodecyl sulfate, and polyvinyl pyrrolidone into deionized water, ball milling for the first time, then adding flaky aluminum oxide for the second ball milling, and after ball milling, dropping isooctyl alcohol to obtain a matrix layer slurry;
[0027] S2, adding nano-particle aluminum oxide, nano-particle zirconium oxide, sodium dodecyl sulfate, and polyvinyl pyrrolidone into deionized water, ball milling for the first time, then adding flaky aluminum oxide for the second ball milling, and after ball milling, dropping isooctyl alcohol into the mixture to obtain a surface layer slurry;
[0028] S3, pouring the surface layer slurry, the base layer slurry, and the surface layer slurry into the mold in sequence and freezing them, pouring and freezing the next time after each freezing, and freeze-drying the green body obtained by three freezing steps to obtain a green body;
[0029] S4, subjecting the green body to heat treatment to remove binder, and then subjecting it to hot pressing and sintering, to obtain the shell-like structure composite ceramic material with prefabricated compressive stress.
[0030] Regarding the selection of raw materials in the present invention, the flaky aluminum oxide is used to imitate the "brick" structure of the shell nacre, and after sintering, the size of the calcite flakes in the shell nacre is similar to that of the shell nacre, and has anisotropic growth characteristics. Nano-alumina particles are used to fill the positions between the alumina "bricks", and the selection of nano-zirconia particles is that their thermal expansion coefficient is lower than that of alumina, which provides a prerequisite for providing prefabricated compressive stress to the surface layer. In addition, zirconium oxide has toughening mechanisms such as phase change toughening and particle dispersion toughening in the material. Sodium dodecyl sulfate (SDS) is used as a dispersant for the slurry, polyvinyl pyrrolidone (PVP) is used as a binder for the slurry, and isooctyl alcohol is used as a defoaming agent for the slurry.
[0031] The layer-by-layer freezing process involved in the present invention is different from the overall freezing casting method, and realizes the layered construction of the shell nacre structure, providing a new means for constructing prestressed ceramic materials. In this process, the oriented arrangement of the flaky aluminum oxide is achieved, so that the interlayer additive phase is dispersed between the flaky aluminum oxide. In the hot pressing sintering process, the densification of the sample and the tighter combination between the layers are completed, and the different thermal expansion coefficients of the layers with different zirconium oxide contents are used to generate prefabricated compressive stress of the matrix on the surface layer during the sintering process.
[0032] The prefabricated compressive stress shell-like structural ceramic composite material constructed by the method of the present invention has multiple intrinsic toughening mechanisms. First, through the layer-by-layer freezing process and hot pressing sintering, the "brick and mud" structure of the shell nacre layer of each layer of the material is successfully constructed; second, nano-zirconia is filled between the alumina "bricks" as the "mud" structure, providing particle dispersion toughening, phase change toughening and other mechanisms; third, during the hot pressing sintering process, the matrix layer has a higher expansion coefficient, and compressive stress is generated on the surface layer during the sintering process, so that the material can withstand higher tensile stress.
[0033] In one or more examples of this implementation mode, in step S2, the mass ratio of flaky aluminum oxide, nanoparticle aluminum oxide, nanoparticle zirconium oxide, sodium dodecyl sulfate, and polyvinyl pyrrolidone is 80:15:5:1:1.
[0034] In one or more examples of this implementation, in step S1, the mass ratio of flaky aluminum oxide, nanoparticle aluminum oxide, nanoparticle zirconium oxide, sodium dodecyl sulfate, and polyvinyl pyrrolidone is 80:5:15:1:1.
[0035] By using different ratios for the base layer and the surface layer, a shell-like structural ceramic composite material with better mechanical properties and compressive stress can be prepared.
[0036] In one or more examples of this embodiment, the nanoparticle zirconium oxide is yttria-stabilized zirconium oxide 3Y-ZrO2, wherein the molar ratio of yttria to zirconium oxide is 3:97, so that the zirconium oxide is stabilized in a tetragonal phase during the sintering process.
[0037] In one or more examples of this embodiment, in step S1, the speed of the first ball milling is 290-310 r / min, and the time is 3-6 h, and the speed of the second ball milling is 290-310 r / min, and the time is 2.9-3.1 h.
[0038] In one or more examples of this embodiment, in step S2, the speed of the first ball milling is 290-310 r / min, and the time is 3-6 h, and the speed of the second ball milling is 290-310 r / min, and the time is 2.9-3.1 h.
[0039] First, the nano-particle aluminum oxide, nano-particle zirconium oxide, sodium dodecyl sulfate, and polyvinyl pyrrolidone are fully ball-milled to make the interlayer phases evenly mixed and well dispersed. Then, the flake aluminum oxide is added and ball-milled for a short period of time to prevent the flake aluminum oxide from breaking during the grinding process and to make the flake aluminum oxide fully contact with the interlayer phases.
[0040] In one or more examples of this embodiment, in step S3, the freeze-drying conditions are to slowly increase the temperature for 48-52 hours at a low temperature and low pressure of -50°C and <1 Pa. The freeze-drying allows the interlayer ice crystals to sublime into gas and be discharged, thereby obtaining a layered porous ceramic body with a directional arrangement structure.
[0041] In one or more examples of this implementation mode, in step S4, the conditions for heat treatment for debinding are to increase the temperature to 600-1300° C. at a rate of 5-10° C. / min and keep the temperature for 2-5 hours.
[0042] In one or more embodiments of this embodiment, in step S4, the hot pressing sintering conditions are: in an argon atmosphere, heating the temperature to 1100°C at a rate of 5-20°C / min, then heating the temperature to 1400-1550°C at a rate of 5-10°C / min, pressurizing to 30MPa, and keeping warm for 1-3 hours.
[0043] The second typical embodiment of the present invention is a shell-like structure composite ceramic material with prefabricated compressive stress obtained by the preparation method as described in the first typical embodiment. The shell-like structure composite ceramic material with prefabricated compressive stress is composed of flaky alumina, nano alumina particles and nano zirconium oxide particles. The particle size of the flaky alumina is 5-11 μm, the particle size of the nano alumina particles is 60-90 nm, and the particle size of the nano zirconium oxide is 30-500 nm.
[0044] The composite ceramic material is a layered imitation shell nacre brick-mud structure. The material is divided into three layers, two surface layers and one matrix layer. Each layer has the "brick-mud" structure of shell nacre, which is made of flaky aluminum oxide stacked into a "brick" structure, and zirconium oxide particles are distributed between the aluminum oxide "bricks". The zirconium oxide content is different in different layers. The zirconium oxide content in the matrix layer is 15wt%, and the zirconium oxide content in the surface layer is 5wt%.
[0045] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in combination with specific embodiments and comparative examples.
[0046] Example 1
[0047] (1) Mixing: 1.8 g of nano-alumina, 5.4 g of nano-zirconium oxide (3Y-ZrO2, 500 nm), 0.36 g of polyvinyl pyrrolidone (molecular weight 5000-10000 g / mol), and 0.36 g of sodium dodecyl sulfate were placed in 18 g of distilled water and mixed at 300 r / min for 6 hours. Then, 28.8 g of flaky alumina was placed in a ball mill and mixed at 300 r / min for 3 hours. The slurry was used as the raw material for the substrate layer. 2.7g of nano-alumina, 0.9g of nano-zirconium oxide (3Y-ZrO2, 500 nanometers), 0.18g of polyvinyl pyrrolidone (molecular weight 5000-10000g / mol), 0.18g of sodium dodecyl sulfate were placed in a ball mill at 300r / min for 6 hours in 18g of distilled water, and then 14.4g of flaky aluminum oxide was placed in a ball mill at 300r / min for 3 hours. Two portions of the above slurry were prepared in two ball mills as raw materials for the surface layer. Three drops of isooctyl alcohol were added to the ball-milled slurry as a defoamer.
[0048] (2) Layer-by-layer freezing: First, pour part of the surface layer slurry into a polytetrafluoroethylene mold with a heat-conducting stainless steel base, pour liquid nitrogen into the incubator to freeze the surface layer, then pour the base layer slurry into it to freeze it, and finally pour part of the surface layer slurry into it to freeze it. The green body that has been frozen layer by layer is placed in a freeze dryer and freeze-dried according to a pre-set program (under the initial condition of -50°C and low temperature and low pressure conditions of <1Pa, slowly heating up for 48 hours) to obtain a green body.
[0049] (3) Heat treatment and sintering: After freeze drying, the green body is taken out and placed in a crucible, which is then placed in a high-temperature box furnace, where the temperature is raised to 1100°C at a rate of 10°C / min and kept at that temperature for 3 hours to complete the debinding. The green body after heat treatment is placed in a graphite mold for hot pressing sintering, and an argon atmosphere is passed through, where the temperature is raised to 1100°C at a rate of 20°C / min, and then raised to 1550°C at a rate of 10°C / min, kept at that temperature for one hour, and a pressure of 30 MPa is applied to complete the sintering process, thereby obtaining a composite ceramic material with a shell-like structure with prefabricated compressive stress.
[0050] The design diagram of the prefabricated compressive stress shell-like structure composite ceramic material is as follows Figure 1 As shown in Figure 1, the surface layer contains less zirconium oxide and has a lower thermal expansion coefficient, resulting in residual compressive stress at the interface between the surface layer and the matrix layer. The SEM images of the surface layer and matrix layer of the shell-like structure composite ceramic material with prefabricated compressive stress are shown in Figure 1. Figure 2 , 3 As shown in the figure, the cross-section of the sample shows that the sample as a whole has the "brick and mud" structure of the shell nacre layer, both in the matrix layer and the surface layer. Due to the processing technology, the orientation of the alumina "bricks" is basically the same, and the zirconium oxide and alumina particles are filled between the alumina "bricks". Figure 3 Compared to Figure 2 It is obvious that the number of zirconium oxide particles in the matrix layer increases, and the phase consistency decreases slightly. Figure 4 As shown in the figure, the shell-like structure composite ceramic material with prefabricated compressive stress has excellent comprehensive mechanical properties, with a bending strength of 430MPa and a fracture toughness of 7.9MPa·m 1 / 2 .
[0051] Example 2
[0052] (1) Mixing: 1.4g of nano-alumina, 7g of nano-zirconium oxide (500 nanometers), 0.3g of polyvinyl pyrrolidone (molecular weight 5000-10000g / mol), and 0.3g of sodium dodecyl sulfate were placed in 37g of distilled water and mixed at 300r / min for 6 hours, and then 19.6g of flaky aluminum oxide was placed in a ball mill and mixed at 300r / min for 3 hours. The slurry was used as the raw material of the substrate layer. 7.56g of nano-alumina, 0.84g of nano-zirconium oxide (30 nanometers), 0.3g of polyvinyl pyrrolidone (molecular weight 5000-10000g / mol), and 0.3g of sodium dodecyl sulfate were placed in 37g of distilled water and mixed at 300r / min for 6 hours, and then 19.6g of flaky aluminum oxide was placed in a ball mill and mixed at 300r / min for 3 hours. Two portions of the above slurry were prepared in two ball mills as the raw material of the surface layer. Three drops of isooctyl alcohol were added to the ball-milled slurry as a defoamer.
[0053] (2) Layer-by-layer freezing: First, pour the surface slurry into a polytetrafluoroethylene mold with a heat-conducting stainless steel base, pour liquid nitrogen into the incubator to freeze the surface layer, then pour the base layer slurry into it and freeze it, and finally pour the surface layer slurry into it and freeze it. The green body that has been frozen layer by layer is placed in a freeze dryer and freeze-dried according to a pre-set program to obtain a green body.
[0054] (3) Heat treatment and sintering: After freeze drying, the green body is taken out and placed in a crucible, which is then placed in a high-temperature box furnace, where the temperature is raised to 1100°C at a rate of 10°C / min and kept at that temperature for 3 hours to complete the debinding. The green body after heat treatment is placed in a graphite mold for hot pressing sintering, and an argon atmosphere is passed through, where the temperature is raised to 1100°C at a rate of 20°C / min, and then raised to 1550°C at a rate of 10°C / min, kept at that temperature for one hour, and a pressure of 30 MPa is applied to complete the sintering process, thereby obtaining a zirconia-alumina composite ceramic material with a shell-like structure having a prefabricated compressive stress.
[0055] Comparative Example 1 (different from the example, this case adopts an integrated freeze-drying process without a layered design)
[0056] (1) Mixing: 4 g of nano-alumina, 7.2 g of nano-zirconium oxide (80 nm), 0.6 g of polyvinyl pyrrolidone (molecular weight 5000-10000 g / mol), and 0.6 g of sodium dodecyl sulfate were placed in a ball mill and mixed at 300 r / min for 6 hours. Then, 44.8 g of flaky alumina was placed in a ball mill and mixed at 300 r / min for 3 hours. Three drops of isooctyl alcohol were added to the milled slurry as a defoaming agent.
[0057] (2) Overall freezing: Pour the slurry into a polytetrafluoroethylene mold with a heat-conducting stainless steel base, and pour liquid nitrogen into an incubator to freeze the slurry. Place the overall frozen green body in a freeze dryer and freeze-dry it according to a pre-set program to obtain a green body.
[0058] (3) Heat treatment and sintering: After freeze drying, the green body is taken out and placed in a crucible, which is then placed in a high-temperature box furnace, and the temperature is raised to 1100°C at a rate of 10°C / min, and the temperature is kept for 3 hours to complete the debinding. The green body after heat treatment is placed in a graphite mold for hot pressing sintering, and an argon atmosphere is passed through, and the temperature is raised to 1100°C at a rate of 20°C / min, and then raised to 1550°C at a rate of 10°C / min, and the temperature is kept for one hour. The pressure is applied at 30 MPa to complete the sintering process, and a zirconia-alumina composite ceramic material with an integrated shell-like structure can be obtained.
[0059] Comparative Example 2 (this case is different from the example in that the difference in zirconium oxide content between the surface layer and the matrix layer is reduced, and the zirconium oxide particle size is adjusted)
[0060] (1) Mixing: 2g of nano-alumina, 3.6g of nano-zirconium oxide (30 nanometers), 0.3g of polyvinyl pyrrolidone (molecular weight 5000-10000g / mol), and 0.3g of sodium dodecyl sulfate were placed in 37g of distilled water and mixed at 300r / min for 6 hours in a ball mill, and then 22.4g of flaky aluminum oxide was placed in a ball mill and mixed at 300r / min for 3 hours. The slurry was used as the raw material for the substrate layer. 2.8g of nano-alumina, 2.8g of nano-zirconium oxide, 0.3g of polyvinyl pyrrolidone (molecular weight 5000-10000g / mol), and 0.3g of sodium dodecyl sulfate were placed in 37g of distilled water and mixed at 300r / min for 6 hours in a ball mill, and then 22.4g of flaky aluminum oxide was placed in a ball mill and mixed at 300r / min for 3 hours. Two portions of the above slurry were prepared in two ball mills as the raw material for the surface layer. Three drops of isooctyl alcohol were added to the ball-milled slurry as a defoamer.
[0061] (2) Layer-by-layer freezing: First, pour the surface slurry into a polytetrafluoroethylene mold with a heat-conducting stainless steel base, pour liquid nitrogen into the incubator to freeze the surface layer, then pour the base layer slurry into it and freeze it, and finally pour the surface layer slurry into it and freeze it. The green body that has been frozen layer by layer is placed in a freeze dryer and freeze-dried according to a pre-set program to obtain a green body.
[0062] (3) Heat treatment and sintering: After freeze drying, the green body is taken out and placed in a crucible, which is then placed in a high-temperature box furnace, where the temperature is raised to 1100°C at a rate of 10°C / min and kept at that temperature for 3 hours to complete the debinding. The green body after heat treatment is placed in a graphite mold for hot pressing sintering, and an argon atmosphere is passed through, where the temperature is raised to 1100°C at a rate of 20°C / min, and then raised to 1550°C at a rate of 10°C / min, kept at that temperature for one hour, and a pressure of 30 MPa is applied to complete the sintering process, thereby obtaining a zirconia-alumina composite ceramic material with a shell-like structure having a prefabricated compressive stress.
[0063] Comparative Example 3
[0064] (1) Mixing: 8.4g of nano-zirconium oxide (500 nanometers), 0.3g of polyvinyl pyrrolidone (molecular weight 5000-10000g / mol), and 0.3g of sodium dodecyl sulfate were placed in 37g of distilled water and mixed at 300r / min for 6 hours, and then 19.6g of flaky aluminum oxide was placed in a ball mill and mixed at 300r / min for 3 hours. The slurry was used as the raw material of the substrate layer. 1.4g of nano-aluminum oxide, 7g of nano-zirconium oxide, 0.3g of polyvinyl pyrrolidone (molecular weight 5000-10000g / mol), and 0.3g of sodium dodecyl sulfate were placed in 37g of distilled water and mixed at 300r / min for 6 hours, and then 19.6g of flaky aluminum oxide was placed in a ball mill and mixed at 300r / min for 3 hours. Two portions of the above slurry were prepared in two ball mills as the raw materials of the surface layer. Three drops of isooctyl alcohol were added to the ball-milled slurry as a defoamer.
[0065] (2) Layer-by-layer freezing: First, pour the surface slurry into a polytetrafluoroethylene mold with a heat-conducting stainless steel base, pour liquid nitrogen into the incubator to freeze the surface layer, then pour the base layer slurry into it and freeze it, and finally pour the surface layer slurry into it and freeze it. The green body that has been frozen layer by layer is placed in a freeze dryer and freeze-dried according to a pre-set program to obtain a green body.
[0066] (3) Heat treatment and sintering: After freeze drying, the green body is taken out and placed in a crucible, which is then placed in a high-temperature box furnace, where the temperature is raised to 1100°C at a rate of 10°C / min and kept at that temperature for 3 hours to complete the debinding. The green body after heat treatment is placed in a graphite mold for hot pressing sintering, and an argon atmosphere is passed through, where the temperature is raised to 1100°C at a rate of 20°C / min, and then raised to 1550°C at a rate of 10°C / min, kept at that temperature for one hour, and a pressure of 30 MPa is applied to complete the sintering process, thereby obtaining a zirconia-alumina composite ceramic material with a shell-like structure having a prefabricated compressive stress.
[0067] The mechanical properties obtained in the above cases are as follows Figure 5 In one or more embodiments of the present invention, in the step 1, the surface layer uses flaky aluminum oxide, nano-aluminum oxide particles and nano-zirconia particles in a mass ratio of 16:3:1, and the base layer uses flaky aluminum oxide, nano-aluminum oxide particles and nano-zirconia particles in a mass ratio of 16:1:3. Under this ratio, Figure 5 It can be seen that the mechanical properties are better. In the case of one-piece freezing or a low difference in the ratio of zirconia between the base layer and the surface layer, prefabricated compressive stress cannot be provided to achieve better mechanical properties.
[0068] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a shell-like structure composite ceramic material with prefabricated compressive stress, characterized in that: The following steps are involved: S1, adding nano-particle aluminum oxide, nano-particle zirconium oxide, sodium dodecyl sulfate, and polyvinyl pyrrolidone into deionized water, ball milling for the first time, then adding flaky aluminum oxide for the second ball milling, and after ball milling, dropping isooctyl alcohol into the mixture to obtain a matrix layer slurry; S2, adding nano-particle aluminum oxide, nano-particle zirconium oxide, sodium dodecyl sulfate, and polyvinyl pyrrolidone into deionized water, ball milling for the first time, then adding flaky aluminum oxide for the second ball milling, and after ball milling, dropping isooctyl alcohol into the mixture to obtain a surface layer slurry; S3, pouring the surface layer slurry, the base layer slurry, and the surface layer slurry into the mold in sequence and freezing them, pouring and freezing the next time after each freezing, and freeze-drying the green body obtained by three freezing steps to obtain a green body; S4, heat-treating the green body to remove binder, and then hot-pressing and sintering to obtain the shell-like structure composite ceramic material with prefabricated compressive stress; In step S1, the mass ratio of flaky aluminum oxide, nanoparticle aluminum oxide, nanoparticle zirconium oxide, sodium lauryl sulfate, and polyvinyl pyrrolidone is 80:5:15:1:1; In step S2, the mass ratio of flaky aluminum oxide, nanoparticle aluminum oxide, nanoparticle zirconium oxide, sodium lauryl sulfate, and polyvinyl pyrrolidone is 80:15:5:1:1; In steps S1 and S2, the molecular weight of the polyvinyl pyrrolidone is 5000-10000 g / mol.
2. The preparation method according to claim 1, characterized in that The nano-particle zirconium oxide is yttria-stabilized zirconium oxide 3Y-ZrO2, wherein the molar ratio of yttria to zirconium oxide is 3:
97.
3. The preparation method according to claim 1, characterized in that: In step S1, the speed of the first ball milling is 290-310 r / min, and the time is 3-6 h. The speed of the second ball milling is 290-310 r / min, and the time is 2.9-3.1 h.
4. The preparation method according to claim 1, characterized in that: In step S2, the first ball milling speed is 290-310 r / min, the time is 3-6 h, and the second ball milling speed is 290-310 r / min, the time is 2.9-3.1 h.
5. The preparation method according to claim 1, characterized in that: In step S3, the freeze-drying conditions are to slowly increase the temperature for 48-52 hours at an initial condition of -50°C and a low temperature and low pressure of <1Pa.
6. The preparation method according to claim 1, characterized in that: In step S4, the conditions for heat treatment for debinding are to increase the temperature to 600-1300° C. at a rate of 5-10° C. / min and keep the temperature for 2-5 hours.
7. The preparation method according to claim 1, characterized in that: In step S4, the hot pressing sintering conditions are as follows: in an argon atmosphere, heating to 1100°C at a rate of 5-20°C / min, then heating to 1400-1550°C at a rate of 5-10°C / min, pressurizing to 30MPa, and keeping warm for 1-3 hours.
8. A composite ceramic material with a shell-like structure and prefabricated compressive stress obtained by the preparation method according to any one of claims 1 to 7, characterized in that: The shell-like structure composite ceramic material with prefabricated compressive stress is composed of flaky aluminum oxide, nano-aluminum oxide particles and nano-zirconia particles. The particle size of the flaky aluminum oxide is 5-11 μm, the particle size of the nano-aluminum oxide particles is 60-90 nm, and the particle size of the nano-zirconia particles is 30-500 nm.
Citation Information
Patent Citations
High-toughness ceramic, preparation method and applications thereof
CN107337450A
Double-toughened composite ceramic material with shell-like structure and preparation method of double-toughened composite ceramic material
CN113004050A